Charity coverage and decreased COVID-19 mortality among uninsured patients in Texas: A retrospective cohort study - Anisha P. Ganguly; John T. Battaile; Michael Harms; Shannon Murray; Tami Gurley; Robert W. Haley; Mamta K. Jain; Kavita P. Bhavan (PLoS ONE, 2025)
Purpose Decreased access to care and social drivers of health have been implicated in COVID-19 disparities. The objective of this study was to test the association between county-funded charity coverage (CFCC) and mortality among uninsured patients hospitalized with COVID-19 in a highly uninsured county. Methods This retrospective cohort study compared electronic health record (EHR) data among uninsured patients hospitalized with COVID-19 in a high-volume safety-net health system in Dallas County, Texas between June 2020 and December 2021. Uninsured patients included CFCC recipients and self-pay patients. We compared mortality over 180 days of follow-up using Cox proportional hazards models, adjusting for gender, age, race/ethnicity, and co-morbidities. Additional outcomes included 90-day mortality, need for mechanical ventilation, and intubation within 24 hours of presentation. Results Among 2,047 patients, 47.0% received CFCC and 53.0% were self-pay. Overall, CFCC patients were older, more likely Hispanic, and had more diagnosed co-morbidities. CFCC patients had decreased adjusted mortality compared to self-pay (aHR 0.61, 95% CI [0.45 to 0.82], p < 0.01), with an absolute risk reduction of 3.3% and a number needed to treat (NNT) with CFCC of 30.4 (95% CI 21.4–66.6). CFCC was associated with lower 90-day mortality compared to self-pay (OR = 0.64, 95% CI [0.45–0.92], p = 0.01), despite similar need for ventilation. Intubation within 24 hours of presentation was lower for CFCC compared to self-pay (OR = 0.46, 95% CI [0.22–0.93], p = 0.03). Conclusions CFCC was associated with decreased mortality among the uninsured hospitalized with COVID-19. The NNT for CFCC to prevent 1 death among uninsured patients was similar to that for standard medications to treat COVID-19. These findings support expanding coverage to improve COVID-19 outcomes.